Perancangan Mesin Pemotong Stick Kentang (French Fries) Kontruksi Vertikal Semi Otomatis - Anderson, Sir; Amri, Khairul; Nofriadi, Nofriadi; Ahmad, Fahdatul; Hanum, Latifa (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2024)
The potato stick-cutting machine is a device that cuts potatoes into long pieces (sticks). This machine can achieve consistent cutting outcomes and rapid cutting times. This is certainly difficult to accomplish manually using hands and knives, especially if the person is inexperienced. This machine's components include a frame, a blade, a knife nest, a cutting disc, a pulley, a V-belt, a pressing lever, a speed regulator, and an electric motor. The potato stick-cutting machine measures 500 mm in length, 300 mm in width, and 700 mm in height. It is driven by a 1 HP motor that is linked to a speed controller to limit its speed. The motor can produce 135 kg of potato sticks per hour using a 2-inch and an 8-inch pulley. The manufacturing cost of this machine is Rp. 4,827,488.00.